Pengaruh Marketing Mix Terhadap Loyalitas Konsumen dengan Variabel Intervening Kepuasan pada Rumah Sakit Jiwa Dr. Radjiman Wediodiningrat - Dyah Sawitri; Martaleni Martaleni; Ayu Bulan Febry KD. (Forum Manajemen Indonesia (FMI), 2016)
At the world of industrialist and service provider, marketing mix is an interesting concept to be explored, because it can lead to a better guidance on how the organization or industry market their products. The aim of the study is to test and analyze the significance and positive effect of marketing mix variable consisting of product, promotion, place, person and process, on customer’s satisfaction, then to test and analyze the significance and positive effect of marketing mix variable consisting of product, promotion, place, person and process on customer’s loyalty. Furthermore the study tests and analyses the significance and positive effect of marketing mix variable consisting of product, promotion, place, person and process on customer loyalty through costumer’s satisfaction at the Outpatient Psychiatric Clinic RSJ Dr. Radjiman Wediodiningrat Mental Hospital. This study is explanatory research using survey as methodology, followed by 100 family caregiver’s schizophrenic patient who is visiting the Outpatient Psychiatric Clinic as respondents of this research. Statistical analysis used in this research is Path Analysis which provide estimates of the magnitude and significance of hypothesized causal connections between sets of variables. Computation of assumption parametric value using SPSS Program 20.0. Result of the study show that there are significance and positive effect of marketing mix variable consisting product, promotion, place, person, process on consumer’s satisifaction at Outpatient Psychiatric Clinic RSJ Dr. Radjiman Wediodiningrat Lawang Mental Hospital, there are significance and positive effect of marketing mix variable consisting product, promotion, place, person, process on consumer’s loyalty at Outpatient Psychiatric Clinic RSJ Dr. Radjiman Wediodiningrat Lawang Mental Hospital. There are significance and positive effect of marketing mix variable consisting product, promotion, place, person, process on consumer’s loyalty through consumer’s satisfaction at Outpatient Psychiatric Clinic RSJ Dr. Radjiman Wediodiningrat Lawang Mental Hospital. Keywords : Marketing mix, satisfaction, loyality